Determinan Internal Dan Eksternal Pembentuk Konsep Diri Masa Remaja: Scoping Review Berbasis Prisma 2009 - Made Deisyana Winaryanta; Galih Gayatri; Shofi Khaqul Ilmy (LPPM ITEKES Mahardika, 2026)
Adolescence is an important period for the formation of self-concept. This review aims to identify internal and external factors that influence adolescent self-concept and serve as a basis for nursing interventions to support healthy psychosocial development. This review was conducted using a scoping review approach based on the 2009 PRISMA protocol, with four databases, namely ProQuest, PubMed, and Google Scholar. The selected keywords were self-concept, self-image, identity, self, self-esteem, and adolescence. Full English-language articles indexed in at least Sinta and published between 2019 and 2025 were included in the inclusion criteria. Fifteen articles were reviewed. The review results show that internal factors such as physical changes related to puberty and childhood trauma affect adolescents' self-concept, as do external factors such as peer support, parenting style, national identity, and exposure to social media. Adolescents are highly vulnerable to psychological stress due to complex physical, mental, and social changes. Nurses, especially in schools and communities, can help adolescents develop a positive and adaptive self-concept by providing psychoeducation, psychosocial screening, counseling, and collaborating with teachers and parents.